Isolation and cloning of ABCH1 gene from rasbora Sarawakensis - Arin Vynona, Robert (Universiti Malaysia Sarawak, (UNIMAS), 2016)
ABC transporter proteins are vital in living organism as they have significant function in transporting molecules across the biological membrane. They are encoded by the ABC genes which comprised several different classes and members in their superfamily. In fish, ABCHI gene might involve in transporting cholesterol or as a multidrug resistance protein. This study aim to identify ABCHI gene in Rasbora sarawakensis and as well as clone it into pGEM-T vector. Extraction of total RNA was done from the whole fish sample using TRI reagent and phenol chloroform precipitation. The cDNA was amplified using designed primer after generated by reverse transcription with PCR. The amplicon with size of 768 bp was then cloned into pGEM-T Easy Vector (Promega). Subsequently, transformation was made using in house prepared E. coli XL-1 Blue competent cells which produced 4.4334 X104 transformants per ug. Double confirmation of the presence of the insert gene was done by colony PCR after the blue white screening. Restriction digestion by using Notl was performed afterward for further confirmation of the insert gene which showed two discreet bands. Sequencing was done after that and the result has proved that ABCHI gene is present in R. sarawakensis as nBLAST has showed 89% similar with ABCHI Danio rerio. This study gives significant values for future study which will provide better understanding on ABCH gene.